Bacterial community improves the volatile components coupled with abiotic factors during the spontaneous fermentation of Chinese strong-aroma Baijiu - Bin Lin; Jie Tang; Qun Li; Liping Zhu; Wei Jiang; Hanbing Ke; Zhang Wen; Huaichen Liu; Shengzhi Yang; Qiang Yang; Shenxi Chen; Peijie Han (Food Chemistry: X)
Flavor components largely depend on microbial activity and environmental conditions during traditional fermented food production. However, the microbial and abiotic contributions to the flavor of Chinese strong-aroma Baijiu (SAB) remain poorly understood. In this study, the composition and functional profiles of the fungal and bacterial communities changed significantly after fourteen days of grain fermentation. Acetilactobacillus jinshanensis, Issatchenkia orientalis and Kazachstani humilis became the dominant species as fermentation proceeded. Pathways related to lipid, protein and secondary metabolite metabolism were enriched during the middle and later stages of grain fermentation. Ethyl caproate, hexyl caproate, and ethyl lactate were identified as the main volatile components in fermented grain. Lactobacillus species were significantly related to volatile components. Compared with fungi, bacterial diversity accounted for 96 % of the variation in volatile components coupled with temperature, acidity and reducing sugar. This work provides insights into the production optimization and flavor enhancement of SAB by optimizing abiotic factors and microbial compositions.